SIKAP DISIPLIN DALAM PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT PADA ANAK USIA 5-6 TAHUN DI TKIT BINA BANGSA ISLAMIC SCHOOL - Harum Nur Ababil; Dian Surya Aprilyanti; Isti Rusdiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze disciplinary attitudes in the implementation of Clean and Healthy Living Behaviors (PHBS) in children aged 5-6 years at TKIT Bina Bangsa Islamic School. The main focus of the study is how discipline is formed through the habit of washing hands, disposing of trash in its place, and maintaining personal hygiene in the school environment. The research approach used was descriptive qualitative with children in group B as the research subjects. Data collection techniques were carried out through participatory observation, in-depth interviews with teachers and the principal, and documentation. The results showed that children's disciplinary attitudes in PHBS had been well formed through consistent habituation methods, examples set by educators, and the support of school facilities. The children's discipline was evident in their awareness of hygiene procedures without the need for repeated instructions, indicating that hygiene values had been internalized as part of their daily character.